2019
DOI: 10.1002/hbm.24776
|View full text |Cite
|
Sign up to set email alerts
|

The impact of task difficulty on the lateralization of processing in the human auditory cortex

Abstract: Perception of complex auditory stimuli like speech requires the simultaneous processing of different fundamental acoustic parameters. The contribution of left and right auditory cortex (AC) in the processing of these parameters differs. In addition, activity within the AC can vary positively or negatively with task performance depending on the type of task. This might affect the allocation of processing to the left and right AC. Here we studied with functional magnetic resonance imaging the impact of task diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…On one hand, the greater involvement of the right temporal lobe in voice than in face recognition could be due to the fact that, in familiarity assessment, the voice requires more complex processing because it relies on a temporal dimension [ 40 , 41 ] that could increase the difficulty of forming stable and well-structured representations, which are necessary to evaluate if a presented voice matches or not with an already known voice. On the other hand, some empirical data gathered by Brechmann and Angenstein [ 42 ] could explain the special link existing between the right temporal lobe and voice identity recognition. These authors have, indeed, studied with fMRI the impact of task difficulty on the degree of involvement of the left and right auditory cortex in the processing of complex auditory stimuli and have shown that task difficulty impacts on the lateralization of processing complex auditory stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, the greater involvement of the right temporal lobe in voice than in face recognition could be due to the fact that, in familiarity assessment, the voice requires more complex processing because it relies on a temporal dimension [ 40 , 41 ] that could increase the difficulty of forming stable and well-structured representations, which are necessary to evaluate if a presented voice matches or not with an already known voice. On the other hand, some empirical data gathered by Brechmann and Angenstein [ 42 ] could explain the special link existing between the right temporal lobe and voice identity recognition. These authors have, indeed, studied with fMRI the impact of task difficulty on the degree of involvement of the left and right auditory cortex in the processing of complex auditory stimuli and have shown that task difficulty impacts on the lateralization of processing complex auditory stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this was also the case for studies showing left > right asymmetries in other contexts 74,75 . Other recent work has found an effect of task difficulty on the lateralization of activity in auditory cortex 76 . Taken together, these studies suggest that the combination of auditory distraction and the difficulty of the segregation/discrimination task may be what underlies left lateralization across such diverse paradigms, supporting a role for left AC in “active listening”.…”
Section: Discussionmentioning
confidence: 84%
“…Everts et al (2009) used the same complex visual search task and also evaluated perfor- One possible explanation for the lack of age-related changes in lateralization for our Puzzle task is that task difficulty influenced the results. In some cases, studies have found correlations between increasing task difficulty and increased activation in the dominant hemisphere (Bodke et al, 2005;Brechmann & Angenstein, 2019;Murphy & Garavan, 2004). In others, the converse pattern is observed; when the task gets more difficult, the sub-dominant hemisphere becomes more involved (Dräger et al, 2004;Fair, 2010;Helton et al, 2010;van Ettinger-Veenstra et al, 2010;Yang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%